1994
DOI: 10.1148/radiology.193.3.7972801
|View full text |Cite
|
Sign up to set email alerts
|

Radiation-induced temporary epilation after a neuroradiologically guided embolization procedure.

Abstract: A 34-year-old woman underwent embolization of a left paraorbital arteriovenous malformation guided with a bi-plane x-ray system in two sessions separated by 3 days. Imaging included 110 minutes of fluoroscopy and 46 digital subtraction angiography acquisitions. Entrance skin dose rates were determined with measurements performed on a skull phantom. The maximum possible skin dose was estimated to be 6.6 Gy, which is consistent with the temporary epilation in the right occipital region of the skull reported by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
47
0
5

Year Published

1996
1996
2013
2013

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(52 citation statements)
references
References 0 publications
0
47
0
5
Order By: Relevance
“…Although there have been several reports analyzing a patient's skin dose in neurointerventional procedures, [1][2][3][4][5][11][12][13][14][15][16][17][18] there are few reports that could demonstrate the regional distribution of skin dose. 5,6,19,20 In this study, we demonstrated that the ESD on the area that encompasses the right temporal and occipital region was considerably higher than that on the frontal region.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there have been several reports analyzing a patient's skin dose in neurointerventional procedures, [1][2][3][4][5][11][12][13][14][15][16][17][18] there are few reports that could demonstrate the regional distribution of skin dose. 5,6,19,20 In this study, we demonstrated that the ESD on the area that encompasses the right temporal and occipital region was considerably higher than that on the frontal region.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, incidences of radiation-induced skin injuries have been reported in neurointerventional procedures, such as embolization of arteriovenous fistulas (AVF), [1][2][3][4] because these complicated interventional radiology procedures tend to require an extended fluoroscopic exposure time and repeated digital subtraction angiography (DSA) with various angles of x-ray projection. In addition, these procedures often need to be performed repeatedly.…”
mentioning
confidence: 99%
“…Long-term outcome studies have not explored the effects of radiation in the patient with subarachnoid hemorrhage, and reports of short-term complications of radiation exposure are limited. 6,[21][22][23] Because the essential question that underlies this and other studies of radiation exposure for this patient group is one of short-and long-term risk, better controlled longitudinal studies are needed to follow patients for the development of skin, lens, thyroid, and cerebral injury or neoplasia.…”
Section: Risk Of Injurymentioning
confidence: 99%
“…The radiation exposure is greater than that during diagnostic angiography due to the prolonged fluoroscopic time and large number of digital subtraction angiography (DSA) frames, and it can induce radiation skin injuries. [1][2][3][4] Although some methods of estimating the skin dose are available, the optimal method for archiving exposure to patients still has to be established. Different methods for the evaluation of entrance skin dose (ESD) and maximum skin dose have been proposed and tested.…”
mentioning
confidence: 99%